(untitled) (Papeles, 2026)
Introduction: Learning activities in English classes are essential, yet they must be aligned with learning objectives and the assessment methods used by teachers. Methodology: This qualitative, descriptive-interpretive study explored the assessment methods employed by English teachers to evaluate the achievement of learning objectives in classroom activities. The sample consisted of seven English teachers from a language center who taught different proficiency levels. Data were collected through semi-structured interviews and classroom observations, and then analyzed using a systematic approach aimed at identifying key themes and recurring patterns. Results and discussion: Findings showed that the assessment methods used were primarily informal and unsystematic, such as open-ended questioning, general monitoring, or spontaneous observation. These practices provided only a broad overview of students’ progress, without allowing for an accurate evaluation of the specific objectives of each activity. Additionally, task supervision lacked systematization, which limited the possibility of offering immediate and constructive feedback. Conclusions: The lack of coherence between learning objectives, instructional activities, and assessment methods negatively affects knowledge acquisition and reduces the effectiveness of teaching.